Faculty Members in Polytechnics to Serve the Community and Industry: Conceptual Skills and Creating Value for the Community—The Two Main Drivers. (September 2021) - Ghasemy, Majid; Mohajer, Leila; Frömbling, Lena; Karimi, Mehrdad
Servant leadership has been proposed as a highly relevant approach to leadership in the higher education context. However, little is known about its contribution to desirable organizational outcomes in academic settings, and even less is known about the role that servant leadership's multidimensionality plays. Consequently, our study aims to investigate the impact of servant leadership's two dimensions (creating value for the community and conceptual skills) on academics' job satisfaction and work motivation. Specifically, we focus on polytechnics due to their significant contribution to the community and industry in developing economies. We applied partial least squares structural equation modeling (PLS-SEM) to analyze the data collected from 228 academics affiliated with Malaysian polytechnics. Our analysis shows that both dimensions of servant leadership are relevant predictors of academics' job satisfaction and work motivation. In addition, while a robustness check confirms the linearity between the variables in our model, the model exhibits a high out-of-sample predictive power, thereby making assumptions about the model relationships' generalizability feasible. We also identified job satisfaction as the most important area of improvement that managerial activities should address.